Screening Protocol of Propofol Infusion Syndrome - Muzaiwirin Muzaiwirin; Arie Utariani (Indonesian Journal of Anesthesiology and Reanimation, 2020)
Introduction: Propofol is often used as sedation for a long time in the ICU. The use is at risk of Propofol Infusion Syndrome (PRIS) which is characterized by arrhythmias or decreased heart function, metabolic acidosis, rhabdomyolysis, and acute renal failure. Literature Review: The pathophysiology of PRIS is due to a disturbance in cell metabolism which inhibits the transport of Free Fatty Acid (FFA) into cells and inhibits the mitochondrial respiration chain. The management of PRIS is supportive of every symptom that arises so that screening is needed as a treatment to reduce high mortality rates. Screening using creatine phosphokinase (CPK) and lactate is supporting data as an initial introduction for symptoms of PRIS. Conclusion: PRIS can occur if continuous administration of propofol > 4 mg / kg / hour. CPK levels> 5000 IU / L become a benchmark to stop propofol before the onset symptoms of PRIS. Implementation of screening protocol is very helpful for clinicians to reduce mortality in ICU due to the use of propofol.